Study of Cultural Characteristics of Clostridioses - Qambarov Abdurauf Abdurasulovich (American Journal of Biology and Natural Sciences, 2025)
clostridiosis, for example, the variety of anatoxins they produce, the fact that they are highly resistant pathogens, the errors and shortcomings in performing each step of the epizootic chain, and the fact that they are widespread in nature. The scientific research work is devoted to the determination of innovative methods of systematic cultural characteristics of clostridia.